Anatomical and clinical predictors of valve dysfunction and aortic dilation in bicuspid aortic valve disease. Issue 7 (1st September 2017) - Evangelista, Arturo; Gallego, Pastora; Calvo-Iglesias, Francisco; Bermejo, Javier; Robledo-Carmona, Juan; Sánchez, Violeta; Saura, Daniel; Arnold, Roman; Carro, Amelia; Maldonado, Giuliana; Sao-Avilés, Augusto; Teixidó, Gisela; et al.
Abstract : Objective: Bicuspid aortic valve (BAV) is associated with early valvular dysfunction and proximal aorta dilation with high heterogeneity. This study aimed to assess the determinants of these complications. Methods: Eight hundred and fifty-two consecutive adults diagnosed of BAV referred from cardiac outpatient clinics to eight echocardiographic laboratories of tertiary hospitals were prospectively recruited. Exclusion criteria were aortic coarctation, other congenital disorders or intervention. BAV morphotype, significant valve dysfunction and aorta dilation (≥2 Z-score) at sinuses and ascending aorta were established. Results: Three BAV morphotypes were identified: right–left coronary cusp fusion (RL) in 72.9%, right–non-coronary (RN) in 24.1% and left–non-coronary (LN) in 3.0%. BAV without raphe was observed in 18.3%. Multivariate analysis showed aortic regurgitation (23%) to be related to male sex (OR: 2.80, p<0.0001) and valve prolapse (OR: 5.16, p<0.0001), and aortic stenosis (22%) to BAV-RN (OR: 2.09, p<0.001), the presence of raphe (OR: 2.75, p<0.001), age (OR: 1.03; p<0.001), dyslipidaemia (OR: 1.77, p<0.01) and smoking (OR: 1.63, p<0.05). Ascending aorta was dilated in 76% without differences among morphotypes and associated with significant valvular dysfunction. By contrast, aortic root was dilated in 34% and related to male sex and aortic regurgitation but was less frequent in aortic stenosis and BAV-RN. Conclusions: Normofunctional valves are more prevalent in BAV without raphe. Aortic stenosis is more frequent in BAV-RN and associated with some cardiovascular risk factors, whereas aortic regurgitation (AR) is associated with male sex and sigmoid prolapse. Although ascending aorta is the most commonly dilated segment, aortic root dilation is present in one-third of patients and associated with AR. Remarkably, BAV-RL increases the risk for dilation of the proximal aorta, whereas BAV-RN spares this area.